Genetic Quality Improvement of Beef Cattle in Indonesia: Overview and Prospects - Rahmatillah, Ririn Siti; Rahmat, Dedi; Dudi, Dudi (JURNAL ILMIAH PETERNAKAN TERPADU, 2024)
Technology for Improving the genetic quality of beef cattle is a key factor in the development of  the livestock industry in Indonesia. In recent decades, efforts have been made to improve beef cattle’s genetic quality through breeding and modern reproductive technologies. The journal aims  to present an in-depth understanding of the efforts made to improve the genetic quality of beef cattle in Indonesia and to explain prospects  in terms of breeding and reproductive technology. This article is based on reflections on recent literature and research in this field..